Hydrazide and Hydrazine Reagents as Reactive Matrices for Matrix-Assisted Laser Desorption/Ionization Mass Spectrometry to Detect Steroids with Carbonyl Groups. Issue 2 (April 2015) - Shigeri, Yasushi; Yasuda, Akikazu; Sakai, Masamichi; Ikeda, Shinya; Arakawa, Ryuichi; Sato, Hiroaki; Kinumi, Tomoya
Fifty-one reagents (37 hydrazides and 14 hydrazines) were examined to determine if they could function as reactive matrices for the detection of steroids with carbonyl groups in matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS). Among these reagents, 3-hydroxy-2-naphthoic acid hydrazide reacted most efficiently with steroids with carbonyl groups, allowing detection of them at the 1 pmol level. Results from accurate mass measurement with a JMS-S3000 Spiral-TOF suggested that the ion peaks corresponding to the protonated fragment of a hydrazone were observed, in addition to the protonated molecular peaks of the resulting hydrazones ([MD + H] + ) and their sodium adduct ([MD + Na] + ). 3-Hydroxy-2-naphthoic acid hydrazide also could detect cortisol (1.93 ng) spiked in a human serum certified reference material, as well as cortisone and cortisol in a human saliva sample collected in the morning. Using a combination of 3-hydroxy-2-naphthoic acid hydrazide and α-cyano-4-hydroxycinammic acid (CHCA) (3-hydroxy-2-naphthoic acid hydrazide:CHCA = 4:1, v/v), even cortisone and cortisol in a human saliva sample collected in the afternoon, when levels are typically low, could be detected effectively.